THE EFFECT OF ALTITUDE ON BREAKING SEED DORMANCY AND STIMULATION OF SEED GERMINATION OF PERSIAN HOGWEED (HERACLEUM PERSICUM) - Khajavi salehani, M.; Mahmoudi, J; Mahdavi, S. Kh.; Habibzadeh, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Persian hogweed is a odorous perennial herb which has pharmaceutical and fodder values. seed is the main propagation method of this species. A seed analysis test was designed to survey the effects of high altitude on breaking dormancy and germination stimulates of Persian hogweed seeds. For this purpose seeds were collected from three different elevations (1700, 2200, 2700 masl) in Kojoor area. After primary cleanings, germination percent(GP) and germination speed (GS) of each elevation were determined by cold stratification compared to control. According to results control seeds were not germinate then seeds of this species need to treat. Statistical analysis of results showed that there are sensible differences between GP and GS of each elevation. As seeds of higher elevation germinate slower and less than higher elevation but in a longer periods. So changes of elevation is an effective factor on germination characteristics of Persian hogweed seeds which have to be considered for every seed collection and rehabilitation program of this species.